(untitled) (Semiárida, 2019)
The objective of this experiment was to evaluate the effects of the addition of crystalline fructose and urea to an annual ryegrassbased diet on microbial protein synthesis, fermentation profile and nutrient apparent digestibility, using continuous culture fermenters. Six fermenters were used in a 3 x 2 factorial arrangement with three levels of water soluble carbohydrates (WSC) obtained by crystalline fructose addition (21, 24 and 27 g.100 g DM1; LWSC, MWSC and HWSC, respectively) and two levels of CP obtained by urea addition (14.6 and 18.6 g.100 g DM1, LCP and HCP, respectively). Four 10d periods were ran sequentially (7d for adaptation, 3d for sampling). Microbial protein synthesis was assessed by purine to N ratio. There was a positive interaction between WSC and CP level on microbial protein synthesis (P<0.001). Water soluble carbohydrate level did not affect fermentation pH, ammonia concentration or total volatile fatty acids concentration (VFA). Greater CP levels also increased acetic acid proportion and tended to increase acetic to propionic acid ratio, whereas WSC level did not affect VFA proportions. Treatments did not affect nutrient digestibility. We conclude that the addition of crystalline fructose to annual ryegrass samples increased microbial protein synthesis at the greater levels of CP in diet.